Effect of smart balance exergame on attention and inhibitory control in healthy young adults using eye-tracking method - Nice, Lee Ja (2021)
Introduction: The over-reliance of technology of the modern society had lead to sedentary lifestyle, resulting in declination of motor and cognitive ability. Effective prevention measure need to be implemented, especially among healthy young adults to prevent these consequences. Recently, it was suggested that exergame, a technology that combined motor training and cognitive training interactively, could be an effective intervention to improve motor and cognitive function. Objective: This study aimed to evaluate the effect of a balance-based exergame on static balance, dynamic balance, selective attention, and inhibitory control of young adults. Methodology: Thirty-two young adults from USM Health Campus, Kelantan were recruited and randomized into either intervention group (n=16) or control group (n=16). Both groups underwent baseline measurement of static balance, dynamic balance, selective attention, and inhibitory control. Then, participants in the intervention group underwent 4 weeks of intervention (FIBOD exergame training) while the control group remained passive for 4 weeks. After 4 weeks, post-intervention measures (similar procedure as baseline measures) were conducted on both groups. Results: Compared to participants in the control group, participants in the intervention significantly improved in static balance test score, dynamic balance test score, reaction time for selective attention task, and reaction time for inhibitory control task after the exergame intervention. However, there was no significant improvement in the accuracy score for inhibitory control task. Conclusion: Exergame intervention is effective in improving static balance, dynamic balance, selective attention, and inhibitory control ability and hence, could be used as an innovative preventive measure to address the consequences caused by sedentary lifestyle.